A 25Mg, 89Y and 115In solid state MAS NMR study of YT2X and Y(T0.5T′0.5)2X (T/T′ = Pd, Ag, Au; X = Mg, In) Heusler phases. Issue 1 (7th December 2016) - Benndorf, Christopher; Stein, Sebastian; Heletta, Lukas; Kersting, Marcel; Eckert, Hellmut; Pöttgen, Rainer
Abstract : Yttrium–transition metal–magnesium (indium) Heusler phases were synthesized from the elements in sealed niobium ampoules in a high-frequency furnace or by arc-melting, respectively. Abstract : Yttrium–transition metal–magnesium (indium) Heusler phases YPd2 Mg, YPd2 In, YAg2 Mg, YAg2 In, YAu2 Mg, and YAu2 In and their quaternary compounds (solid solutions) Y(Pd0.5 Ag0.5 )2 Mg, Y(Pd0.5 Ag0.5 )2 In, Y(Pd0.5 Au0.5 )2 Mg, Y(Pd0.5 Au0.5 )2 In, Y(Ag0.5 Au0.5 )2 Mg and Y(Ag0.5 Au0.5 )2 In were synthesized from the elements in sealed niobium ampoules in a high-frequency furnace or by arc-melting, respectively. All compounds crystallize with the cubic MnCu2 Al type structure (Heusler phase), space group Fm 3̄ m . The structure of Y(Ag0.39 Au0.61 )2 Mg was refined from single crystal X-ray diffractometer data: a = 689.97(5) pm, w R 2 = 0.0619, 52 F 2 values, 6 parameters. Magnetic susceptibility measurements show Pauli paramagnetic behavior for all samples. The compounds were investigated by 25 Mg, 89 Y and 115 In solid state MAS NMR spectroscopy. Large positive resonance shifts are observed for all nuclei. A review of the present data in the context of literature data on isotypic Heusler phases with Cd and Sn indicates that the 89 Y shifts show a correlation with the electronegativity of the main group atoms (Mg, Cd, In, Sn). The solid solutions Y(Ag1− x T x )2 Mg ( x = 0.1, 0.25, 0.33, 0.5; T = Pd, Au) clearly show Vegard-like behavior concerning their lattice parameters, and their main group element resonance shifts arising from spin and orbital contributions are close to the interpolated values of the corresponding end-member compounds.